A Comprehensive analysis of Neonatal pain and measures to reduce pain - Hardeep Kaur; Gaurav Mahajan (Wolters Kluwer Medknow Publications, 2019)
Pain management of neonates is much debated topic in the medical field. Pain and particularly chronic pain may affect the development of the brain and cause permanent injuries. Neonates being non-verbal are unable to express their pain and thus are exposed to various painful procedures without adequate pain relief. This lack of self-report, inadequate pain assessment tool, lack of awareness and concern amongst the care providers and non-availability of standard protocols lead to inadequate pain relief in neonates. The communication of infant pain is identified through validated tools such as: Premature Infant Pain Profile (PIPP), Neonatal Facial Coding System (NFCS), and the Neonatal Infant Pain Scale (NIPS). The most popular means of reducing minor procedural pain is oral glucose solution, music therapy, cuddling the neonates, breast feeding and use of topical anaesthetic agents. Topical anaesthetic agents that are commonly used like EMLA are not far from side effects. EMLA is known to cause methemoglobinemia in preterm babies. Recently a study has been conducted using 4% Liposomal Lidocaine at a tertiary care centre in India by Kaur et al which has found this agent to be useful to relieve minor procedural pain like Venepuncture and found it to be free from side effects of methaemoglobinaemia.[18] In nutshell, effective management of pain is an ethicals well as a scientific issue. Is it not humane to think about providing adequate pain relief to such tiny non-verbal human beings? Effective pain assessment and management in infants correlates with the quality of healthcare provided and the professionalism shown by healthcare providers. As part of comprehensive pain prevention program, each neonatal unit should develop strategies to provide effective pain relief for all procedures.